2016
DOI: 10.1097/aap.0000000000000372
|View full text |Cite
|
Sign up to set email alerts
|

Update on Ultrasound for Truncal Blocks

Abstract: Since our last review, numerous studies have been published, especially for the paravertebral and transversus abdominis plane blocks, and 3 novel US-guided blocks (Pecs, quadratus lumborum, and transversalis fascia blocks) have been described. Although some of these studies support the use of US for performing these blocks, others do not. Additional studies have used US to improve our understanding of the anatomy pertinent to these blocks and evaluated the effect on patient outcomes and risk of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(47 citation statements)
references
References 63 publications
0
43
0
4
Order By: Relevance
“…Specific methodologies for the various components of this project are detailed in the accompanying individual articles. [2][3][4][5][6][7][8][9] In brief, putative evidence was gathered using a variety of standard electronic search engines to identify relevant literature, concentrating on the period from 2009 through spring 2015. The specific search engines used, language limitations, and MeSH (medical subject headings) are described in the individual articles.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specific methodologies for the various components of this project are detailed in the accompanying individual articles. [2][3][4][5][6][7][8][9] In brief, putative evidence was gathered using a variety of standard electronic search engines to identify relevant literature, concentrating on the period from 2009 through spring 2015. The specific search engines used, language limitations, and MeSH (medical subject headings) are described in the individual articles.…”
Section: Methodsmentioning
confidence: 99%
“…We have also included in this iteration analysis of evidence for newer truncal blocks-PECS, quadratus lumborum, and transversalis fascia-all of which have been described in limited case reports or technical descriptions without comparison to alternative techniques or with insufficient subject numbers to adequately ascertain complication rates or major outcomes. 7 Our 2010 review 53 concluded that limited RCT evidence supported USG as the preferred technique for rectus sheath and II/IH blocks, but evidence was insufficient to make recommendations regarding other blocks. The interval 5-year period has produced a number of anatomic (primarily cadaver based), pharmacokinetic, injectate spread, and feasibility studies, but relatively few studies that compared UGRA with other localization techniques or that assessed complications.…”
Section: Truncal Blocksmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple recently published systematic reviews found ultrasound guidance to improve the performance of the blocks and different patient outcomes [11][12][13][14]. Importantly, the expectation that direct visualization of the neural structures would reduce the incidence of neurologic complications has not been confirmed, but ultrasound guidance has been found to reduce the risk of local anesthetic systemic toxicity and possibly pneumothorax [15 & ].…”
Section: Alternatives To Neuraxial Analgesiamentioning
confidence: 99%